Changing knowledge, changing technology: implications for teacher education futures. Issue 1 (1st January 2016) - Burden, Kevin; Aubusson, Peter; Brindley, Sue; Schuck, Sandy
Abstract : Recent research in teacher education futures has identified two themes that require further study: the changing nature of knowledge and the changing capabilities of technologies. This article examines the intersection of these two themes and their implications for teacher education. The research employed futures methodologies based on scenario creation. With a focus on the above themes or dimensions, a panel of experts was interviewed to draw on its collective wisdom to explore alternative teacher education futures. Data from these interviews were analysed to stimulate the construction of four future teacher education scenarios. Feedback on the scenarios was obtained from teacher educators in Europe and Australia. The scenarios were then revised based on this feedback. The final scenarios are presented here as a way of provoking discussion among teacher educators about teacher education futures.